LLT1-CD161 Interaction in Cancer: Promises and Challenges - Braud, Veronique M.; Meghraoui-Kheddar, Aïda; Elaldi, Roxane; Petti, Luciana; Germain, Claire; Anjuère, Fabienne (Frontiers in Immunology, 2022)
The success of immune checkpoint therapy in cancer has changed our way of thinking, promoting the design of future cancer treatments that places the immune system at the center stage. The knowledge gained on immune regulation and tolerance helped the identification of promising new clinical immune targets. Among them, the lectin-like transcript 1 (LLT1) is the ligand of CD161 (NKR-P1A) receptor expressed on natural killer cells and T cells. LLT1/CD161 interaction modulates immune responses but the exact nature of the signals delivered is still partially resolved. Investigation on the role of LLT1/CD161 interaction has been hampered by the lack of functional homologues in animal models. Also, some studies have been misled by the use of non-specific reagents. Recent studies and meta-analyses of single cell data are bringing new insights into the function of LLT1 and CD161 in human pathology and notably in cancer. The advances made on the characterization of the tumor microenvironment prompt us to integrate LLT1/CD161 interaction into the equation. This review recapitulates the key findings on the expression profile of LLT1 and CD161, their regulation, the role of their interaction in cancer development, and the relevance of targeting LLT1/CD161 interaction.